Mitochondrial damage and apoptosis: Key features in BDE-153-induced hepatotoxicity - Pereira, Lilian Cristina [UNESP]; Cabral Miranda, Luiz Felipe; Franco-Bernardes, Mariana Furio; Tasso, Maria Julia; Duarte, Filipe Valente; Inácio Varela, Ana Teresa; Rolo, Anabela Pinto; Marques Palmeira, Carlos Manuel; Dorta, Daniel Junqueira [UNESP] (Elsevier, 2018)
Brominated flame retardants are used in consumer goods to increase product resistance to fire and/or high temperatures. Polybrominated diphenyl ethers (PBDEs) are the most commonly employed class of brominated flame retardants because they are inexpensive and can effectively prevent flame from spreading. PBDEs are persistent, can bioaccumulate, are transported over long distances, and display toxicity. However, their toxic mechanisms of action have not been well established. Because mitochondria are recognized as the main energy-producing cell organelle and play a vital role in cellular function maintenance, here we apply mitochondria as an experimental model to evaluate the toxic effects of the PBDE congener BDE-153 (Hexa-BDE) at concentrations ranging from 0.1 to 25 μM. We also assess BDE-153 cytotoxicity to HepG2 cells in order to elucidate its mechanisms of toxicity. Exposure to BDE-153 affects isolated mitochondria: this congener can interact with the mitochondrial membrane, to dissipate the membrane potential and to induce significant ATP depletion. Furthermore, BDE-153 can diminish MTT reduction and cell proliferation and can interfere in cell cycle, as evaluated in cell cultures. These cytotoxic effects are related to mitochondrial dysfunction due to mitochondrial membrane potential dissipation and reactive oxygen species accumulation. These effects result in apoptotic cell death, as demonstrated by phosphatidylserine maintenance on the cell membrane external surface, nuclear condensation and fragmentation, and presence of pro-apoptotic factors such as cytochrome c and Apoptosis-inducing Factor (AIF) plus caspase 3 activation in the cytosol. Together, our results show PBDEs can induce cytotoxicity, reinforcing the idea that these compounds pose a risk to the exposed population.